Comunicación comunitaria en las organizaciones sociales sector La Chiquita, perteneciente al cantón El Empalme, año 2020 - Valencia Tuarez, Nicole Stefania (2021)
Community communication is an important axis for building and sharing people's voice, providing the word to the community, neighborhood, social sector, youth, children, organizations, communities, educational units; teach them to do their own communication and at the same time build a community communication according to the needs, situations and requests of the social sectors. It must be understood that community communication is not only a communication particularly from a locality, sector or community of peoples and nationalities, nor from a peasant community. We think that it is not delimited by the physical territory. Community communication is a new form of communication, it is a new vision, it is a new communicational paradigm, it is a process of communicational construction based on principles and values of community coexistence that become a space to exercise human rights. It is an intermediate of popular, community, alternative, collective and participatory expression. It is a process to generate knowledge, critical thoughts, awareness, sensitivity, active and purposeful commitment as a strategic axis to achieve the common good, social justice, equity and peaceful coexistence. The community communication that we propose is a curve, which is based on a process that must be in permanent flow with information, training, production, and realization. Interaction with people, media construction, dialogue and specifically the commitment to create new content, languages, narratives, investigative and aesthetic processes, is a workplace and creative-artistic expression with new ways of relating to people and with new approaches; with horizontal, democratic understandings and coexistence, committed to new ways of communicating with people. This research project on community communication has the fundamental objective of promoting communication and social participation within the community of the La Chiquita sector so that they have a better social organization. In the development of this research work, participatory field research and bibliographic research were used, the techniques for collecting information was the survey of all the inhabitants of the La Chiquita sector.